2016
DOI: 10.1001/jamacardio.2015.0252
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Cardiac Remodeling in US Professional Basketball Players

Abstract: This study provides normative cardiac data for a group of athletes with greater anthropometry than any previously studied athlete group and for a group known to have elevated rates of sudden cardiac death. These data can be incorporated into clinical assessments for the primary prevention of cardiac emergencies in basketball players and the athletic community at large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 41 publications
9
64
1
Order By: Relevance
“…In comparison with ordinary mature, basketball players have grand left ventricle, a similar result was found in participants in various sport activities (Engel et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…In comparison with ordinary mature, basketball players have grand left ventricle, a similar result was found in participants in various sport activities (Engel et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Indexing aortic size for BSA is proposed as an additional/alternative means of recognizing aortic dilation which accounts for anthropometrics; however, it is widely recognized that at the upper extremes of body size there is a plateauing of aortic size elegantly described by Engel et al in a study of 526 National Basketball Association athletes amongst other studies 8, 16, 22, 23 . Recent data also suggests the aortic cross-sectional area/height ratio is a robust predictor of outcome 24, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that 27.4% of professional basketball athletes met LVH criteria by echocardiography [9]. This study, which included 529 athletes, does not mention any EKG associations.…”
Section: Lbbb Inmentioning
confidence: 98%